2023
DOI: 10.1186/s12964-023-01110-7
|View full text |Cite
|
Sign up to set email alerts
|

Change in cytokine profiles released by mast cells mediated by lung cancer-derived exosome activation may contribute to cancer-associated coagulation disorders

Abstract: Background Coagulation disorders are a significant cause of lung cancer mortality. Although mast cells are known to play a role in coagulation abnormalities, their specific role in this process has not yet been elucidated. Method We detected mast cells in the tumor microenvironment using single-cell sequencing data and examined their correlation with thrombosis-related genes, neutrophil-related genes, neutrophil extracellular trap-related signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It had been extensively reported that lung cancer, especially for LUAD, could frequently cause coagulation aberration and even venous thromboembolism, which was a major cause of cancerrelated deaths (25)(26)(27)(30)(31)(32). It has been proved that the TME plays a significant role in tumor progression and therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It had been extensively reported that lung cancer, especially for LUAD, could frequently cause coagulation aberration and even venous thromboembolism, which was a major cause of cancerrelated deaths (25)(26)(27)(30)(31)(32). It has been proved that the TME plays a significant role in tumor progression and therapy.…”
Section: Discussionmentioning
confidence: 99%